The third force - Alan Powell (Oxford University Press, 2003)
The Australian New Guinea Administrative Unit (ANGAU), an Australian Army unit, superseded the civilian government of Papua New Guinea early in 1942 and administered the area until mid-1946. This book traces all major aspects of ANGAU's war. It provides the only full-length study of Papua New Guinean interaction with Australian and American armed forces in the Second World War, filling a considerable gap in the study of Australia's colonial administration and in New Guinea's political and military history